Intelligent Tutoring Systems 10th International Conference, ITS 2010, Pittsburgh, PA, USA, June 14-18, 2010, Proceedings, Part II - Aleven, Vincent; Kay, Judy.; Mostow, Jack.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The books (LNCS 6094 and 6095) constitute the refereed proceedings of the 10th International Conference on Intelligent Tutoring Systems, ITS 2010, held in Pittsburgh, PA, USA, in June 2010. The 61 revised full papers, 5 invited talks, and 58 short papers presented were carefully reviewed and selected from 186 submissions. The papers are organized in topical sections on educational data mining, natural language interaction; ITS in Ill-defined domains; inquiry learning, collaborative and group learning; intelligent games; gaming the system; pedagogical strategies; affect; games and augmented reality; pedagogical agents, learning companions, and teachable agents; intelligent tutoring and scaffolding; metacognition; and authoring tools and theoretical synthesis.
Affect 2 -- Educational Data Mining 2 -- Natural Language Interaction 2 -- Authoring Tools and Theoretical Synthesis -- Collaborative and Group Learning 2 -- Intelligent Games 2 -- Intelligent Tutoring and Scaffolding 2 -- Young Researchers Track -- Short Papers -- Interactive Events.
Keywords: Computer science; Multimedia systems; Artificial intelligence; Text processing (Computer science; Social sciences -- Data processing; Education; Computer Science; Computers and Education; User Interfaces and Human Computer Interaction; Multimedia Information Systems; Computer Appl. in Social and Behavioral Sciences; Document Preparation and Text Processing; Artificial Intelligence (incl. Robotics).